Treatment of digital dermatitis using salicylic acid in European bison (Bison bonasus) reveals promising results - Jucker, Simone; Alsaaod, Maher; Steiner, Adrian; Zingre, Tatiana; Kaessmeyer, Sabine; Gurtner, Corinne; Friker, Brian; Brandt, Sabine; Jensen, Tim K.; Hoby, Stefan (Frontiers in Veterinary Science, 2022)
Digital dermatitis (DD) associated with the presence of multiple Treponema spp. was recently described for the first time in European bison (Bison bonasus). DD is characterized by skin inflammation in the distal foot area in various ungulates. The objective of this proof of concept study was to test a treatment protocol adopted from cattle for its applicability in this wildlife species using five animals. Keratolytic salicylic acid paste was administered topically under bandages for seven days to enable removal of the affected skin. All interventions were performed under general anesthesia. To evaluate the treatment efficacy, photographs and biopsies were taken pre- and post-treatment. The biopsies were examined histologically, by PCR for the presence of different bacterial species, by Treponema-specific fluorescent in situ hybridization (FISH), and by transmission electron microscopy. Based on photographs, complete clinical healing of the 15 feet with macroscopical DD lesions was achieved. Histological examination showed mild to moderate dermatitis in 17/20 feet before, and in 12/20 feet after treatment. 17/20 feet were Treponema spp. PCR positive before, and none was positive after treatment. Dichelobacter nodosus, Fusobacterium necrophorum, and Porphyromonas levii could not be detected in any of the samples. By FISH and electron microscopy, Treponema spp. could be visualized in the stratum corneum before, but not after treatment. These results suggest that this treatment method can be applied as standard practice prior to transporting DD affected European bison to prevent the spread of this contagious disease.